MAKNA DAN IMPLIKASI SOSIAL PASAHAT TITI MARANGKUP DALAM PERKAWINAN BUKAN MARPARIBAN BAGI SUKU BATAK TOBA (Studi Kasus di Desa Tanoh Subukh, Kabupaten Aceh Tenggara) - Pipiana, Rudmeida; Zuryani, Nazrina; Mahadewi, Ni Made Anggita Sastri (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 2 No 01 (2022): JISSOROT, 2022)
The ideal marriage for the Toba Batak is a marpariban marriage, namely taking a wife from the mother's clan. The pasahat titi marangkup tradition is carried out to respect and ask for the blessing of the uncle because his nephew does not intend to marry the uncle's daughter. An uncle in a Toba Batak marriage must attend his nephew's wedding, however, when the uncle is unable to attend, he is replaced with a substitute uncle. The research approach uses expolative qualitative. The theory used as a scalpel in the implementation of this research is the constructivism theory of Clifford Geertz which asserts that humans are symbolic creatures, in symbols there are meanings that are produced and these meanings form a cultural network. The conclusion of the study explains that the pasahat titi marangkup tradition must be carried out in non-marpariban marriages in Tanoh Subukh Village, Southeast Aceh Regency.